2022
DOI: 10.3390/agriculture12020295
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Storage Potential of Agroforestry System near Brick Kilns in Irrigated Agro-Ecosystem

Abstract: The current study was conducted to estimate the carbon (C) storage status of agroforestry systems, via a non-destructive strategy. A total of 75 plots (0.405 ha each) were selected by adopting a lottery method of random sampling for C stock estimations for soil, trees and crops in the Mandi-Bahauddin district, Punjab, Pakistan. Results revealed that the existing number of trees in selected farm plots varied from 25 to 30 trees/ha. Total mean tree carbon stock ranged from 9.97 to 133 Mg C ha−1, between 5–10 km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…A forest ecosystem is dominated by perennial vegetation, with higher carbon stocks playing a crucial role in the carbon cycle and helping to mitigate climate change [3,4]. However, the rapid growth of urbanization and anthropogenic activities has lead to deforestation, land use change, loss of biodiversity, and forest degradation [5,6]. The contribution of trees to improving livelihoods and providing ecosystem services cannot be ignored, and management of resources through agroforestry can provide a nature-based solution to synergize adaptation and mitigation strategies to meet forest-based needs [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A forest ecosystem is dominated by perennial vegetation, with higher carbon stocks playing a crucial role in the carbon cycle and helping to mitigate climate change [3,4]. However, the rapid growth of urbanization and anthropogenic activities has lead to deforestation, land use change, loss of biodiversity, and forest degradation [5,6]. The contribution of trees to improving livelihoods and providing ecosystem services cannot be ignored, and management of resources through agroforestry can provide a nature-based solution to synergize adaptation and mitigation strategies to meet forest-based needs [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the rapid growth of urbanization and anthropogenic activities has lead to deforestation, land use change, loss of biodiversity, and forest degradation [5,6]. The contribution of trees to improving livelihoods and providing ecosystem services cannot be ignored, and management of resources through agroforestry can provide a nature-based solution to synergize adaptation and mitigation strategies to meet forest-based needs [6]. Agroforestry has been proposed as a global solution to improving land use by reducing environmental impacts and financial risks for farmers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Productivity in plantation is higher (3.2 Mg ha/1 year) than productivity of natural forest (1.1 Mg ha/1 year), so it can benefit from better silvicultural techniques than a wild forest (Lal and Singh, 2000). Additionally, resource management through agroforestry may offer a natural way to synchronise the implementation of adaptation and mitigation measures with the satisfaction of forest-based needs (Komal et al, 2022). Agroforestry has been acknowledged as a GHG mitigation strategy under the Kyoto Protocol because it is an integrated approach (Birhane et al, 2020;Das et al, 2020;Sarkar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the C accumulation in C4 grassland was lower than previously thought. On the other hand, Komal et al [2] investigated the soil C accumulation potential of agroforestry in the eastern region of Pakistan, which is exposed to the major impacts of climate change due to global warming. They found that C storage potential differed among tree species and observed that woody vegetation C stock was comparable to soil C stock.…”
mentioning
confidence: 99%